LIVED EXPERIENCES OF MOOCERS: A PHENOMENOLOGICAL STUDY - Aseoche, Hilda Habacon; Bandoy, Marcial M (PUPIL: International Journal of Teaching, Education and Learning, 2021)
This study involved educators who took online courses under MOOC or Massive Open Online Course sponsored by the U.S. Department of State in partnership with the Regional English Language Office (RELO) in the Philippines. It focused on the essence of the lived experiences of a MOOCer. Findings reveal that teachers may find MOOC a venue for the continuous and sustainable training platform where they could discover new approaches, strategies, and effective methodologies for the improvement of the teaching-learning process. MOOC will serve as the common milieu for teachers to meet new acquaintances, friends, noted personalities, authors, and trainers. The new knowledge, skills, and attitude developed through time as they continuously hold with the tenets of MOOC will bring them a place in the domain of education and training. The hunger for the latest ideas and information brought about by internalizing the ideals of MOOC will drive them more to discover new ways of thinking, teaching, and sharing thoughts for the betterment of learning school children. MOOC will become the hub for personality development and the attitude of the ideal teacher of tomorrow.